Estetika Hindu Dalam Lontar Aji Ghurnnita - Ariyasa Darmawan (Jnanasiddhanta : Jurnal Teologi Hindu, 2022)
Karawitan comes from the word rawit which means smooth or beautiful, to karawitan which means the art of instrumental and vocal sound using the barrel or scales of pelog and selendro. Balinese instrumental karawitan is called gamelan, and vocal karawitan is called tembang or sekar.               Hindu aesthetics is essentially a perspective on the sense of beauty that is bound by Hindu religious values based on the teachings of the Vedic scriptures. There are several concepts that would become an important foundation of Hindu aesthetics, namely purity (Shiwam), truth (Satyam), and balance (Sundaram). Holiness (Shiwam) is essentially about divine values which also includes Yajña and taksu. Truth (Satyam) includes the values of honesty, sincerity, and sincerity. Balance (Sundaram) which includes similarities and differences can be reflected in several dimensions.               Aesthetic reflection with the concept of balance that has two dimensions can produce symmetrical forms that are at the same time asymmetrical or harmonious and disharmony relationships which are commonly called rwa bhineda. Balance in the three dimensions is closely related to the concept of Hindu cosmology which divides this world into three parts: upper, middle, and lower which is commonly known as Tri Bhuwana. The underworld (Bhur loka) is the world of bhuta kala, the middle world (Bhwah loka) which is the realm between the human world and the rest of the world, and the upper world (Shwah loka) is the world of God and the gods.            The balance of the two Balinese musical arts that is often mentioned in Lontar Aji Ghūrṇnita is the existence of pelog and selendro barrels, ngumbang ngisep, lanang and wadon, as well as the concept ofbaikan or patet or saih. The balance of the three Balinese musical arts mentioned in Lontar Aji Ghūrṇnita is the concept of tri angga, consisting of pengawit or percussion opening, pengawak or percussion body, and pressing or closing the percussion.